ANALISIS LUAS MINIMUM USAHATANI KRISAN BUNGA POTONG (Chrysanthemum Indicum L.) (Kasus Di Kecamatan Bandungan Kabupaten Semarang Provinsi Jawa Tengah) - Puji Waluyo (Fakultas Pertanian UST, 2017)
This study aims to determine farm income, Farmers Exchange Rate (NTP) is the ratio between the index of prices received by farmers (It) and the index of prices paid by farmers (Ib) of chrysanthemum farm, as well as the minimum land area of farms to be established, if the target per capita income for 2020 amounted to US 10,000 or approximately Rp 114.250.000,-/year. The basic method used in this research is descriptive analysis. Techniques used in this research is a survey research techniques. Method of determining the location done intentionally (purposive) that is in District Bandungan Semarang regency of Central Java province. Sample selection methods using systematic random sampling technique. Data analysis method used is the analysis of revenue and production costs, analysis of Farmers Exchange Rate (NTP) and statistical testing. The survey results revealed that: (1) Average farm income chrysanthemum in District Bandungan mathematically already exceeded the per capita income target set by the Ministry of Finance of the Republic of Indonesia in 2020, which amounted to US 10,000 or approximately Rp 114.250.000, - / year, but the test results are not statistically significant say or untrustworthy. (2) Farmers Exchange Rate (NTP) chrysanthemum in Sub Bandungan higher than the Farmers Exchange Rate (NTP) the overall results of the calculation BPS Semarang District in 2013 which amounted to 115.06. (3) The minimum land area of chrysanthemum farm in the district Bandungan mathematically has been reached in the amount of 2361.223 m2, but the test results are not statistically significant say or untrustworthy.Â Keywords: chrysanthemum, farming, income, farmers